History of the 33d Iowa Infantry Volunteer Regiment, 1863-6 - Sperry, A. F. (Andrew F.), 1839-1911 (Book collections on Project MUSE., 1999)
"As the regiment's fife and drum major responsible for sounding the duty calls that regulated a soldier's day, Sperry was well situated to observe the inner workings of his unit. His perceptive narrative of army life on the march and in camp captures the courage, humor, and sufferings of the rank and file. Although he took pride in his regiment's accomplishments, he unflinchingly reveals the hard side of war with vivid depictions of looting, resistance to orders, and "extermination" of Confederate guerrillas." "Sperry's memoir is made more valuable by the new introduction and detailed notes from the editors. Their meticulous annotations include quotes from the diaries, letters, and reminiscences of other soldiers, adding depth and detail to the account."--Jacket.